2016
DOI: 10.2174/1573396312666160831143951
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Bronchopulmonary Aspergillosis: AllA Radiologist Needs To Know

Abstract: In recent years, role of radiology in ABPA has evolved. Radiology plays an important role not only in diagnosis but also classification and prognostication of the disease. A radiologist should also be familiar with the clinical spectrum and laboratory findings of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Radiological findings in ABPA patients include migratory pulmonary infiltrates, central bronchiectasis, sub-segmental or segmental collapse, and centrilobular nodules. 11 In tuberculosis-endemic settings, misdiagnosis of ABPA as tuberculosis and vice versa is not uncommon. This is due to the overlapping symptoms and radiological findings of both conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Radiological findings in ABPA patients include migratory pulmonary infiltrates, central bronchiectasis, sub-segmental or segmental collapse, and centrilobular nodules. 11 In tuberculosis-endemic settings, misdiagnosis of ABPA as tuberculosis and vice versa is not uncommon. This is due to the overlapping symptoms and radiological findings of both conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Mucoid impaction may obstruct the lobar bronchi, leading to the finger-in-glove sign with lobar atelectasis seen on chest radiography. Lobar or segmental lung collapses have been described in 14–39% of patients with ABPA [ 6 8 ]. Our study showed that total lung collapse could also be a manifestation of ABPA although it is less frequently reported in the literature [ 9 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the diagnosis of ABPA may be supported by the presence of typical radiologic findings. The most common CT-scan findings are mucoid impactions and bronchiectasis predominantly involving the segmental and subsegmental bronchi of the upper lobes, with centrilobular nodules [ 6 8 ]. In case of total unilateral lung collapse, these imaging findings should be investigated in the contralateral lung.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations